What is the optimal condition for fertilization of IVM oocytes?. (10th August 2012) - Funahashi, Hiroaki
Abstract: Application of in vitro maturation (IVM) is recently increasing for human infertility, especially to rescue patients of polycystic ovarian syndrome and ovarian hyperstimulation syndrome. To increase the application of IVM oocytes for embryo production and the efficiency of successful production of babies using IVM oocytes, quality control of oocytes and achievement of fertilization in the most suitable condition may be very important. In this paper, suitable conditions for fertilization of IVM oocytes will be discussed with recent knowledge about IVM and in vitro fertilization of oocytes in domestic animals. Currently, human oocytes are collected mainly from patientsˈ ovaries 36 h following mild gonadotropin stimulation and used for IVM for 24–26 h. However, asynchronous progression of those oocytes to reach the metaphase‐II stage may have occurred during the IVM culture. In the oocytes that have already progressed to the metaphase‐II stage, sudden aging such as reduction in maturation promoting factor and MAP kinases will start to occur. Application of specific inhibitors of phosphodiesterase to control intracellular cAMP (cyclic adenosine monophosphate) level may be effective to synchronize timings of the germinal vesicle breakdown and consequently the meiotic progression of oocytes, and to improve the developmental competence. Furthermore, treatment of aging oocytes with caffeine appears to rescue them from reductions in maturation promoting factor and MAP kinases and to improve the developmental competence. Assessment methods to select oocytes with good quality may also be important to improve the successful rates.